Development of Smart Beater and Pole Base Kasti Ball Game for Elementary School - Radika Aditia; Muhammad Isnandar (Joska: Jurnal Isori Kampar, 2025)
Objectives: Traditional Indonesian Kasti ball games require modernization to enhance student engagement and learning outcomes in elementary physical education. Current equipment limitations and safety concerns necessitate innovative solutions that maintain cultural authenticity while improving functionality. This research aimed to develop and evaluate the effectiveness of smart beater and pole base modifications for Kasti ball games in elementary school settings, focusing on student engagement, skill development, and safety improvements. Methods: A quasi-experimental study was conducted with 120 elementary students (ages 8-12) from SD Negeri 105290 Desa Kolam, North Sumatra. Participants were divided into control (traditional Kasti) and experimental (smart beater and pole base Kasti) groups. Data collection included motor skill assessments, engagement surveys, and safety incident reports over 12 weeks. Statistical analysis employed SPSS 25.0 using independent t-tests and ANOVA. Results: The experimental group showed significant improvements in batting accuracy (p<0.001), game engagement scores (p<0.01), and reduced injury incidents (87% decrease). Smart beater technology enhanced hitting precision by 34%, while the pole base system improved field organization and reduced setup time by 45%. Conclusion: Smart beater and pole base modifications successfully enhanced traditional Kasti ball games, improving student performance, engagement, and safety without compromising cultural authenticity. Implementation recommendations include teacher training and gradual integration protocols.